A novel approach for simultaneous analysis of perchlorate (ClO4−) and bromate (BrO3−) in fruits and vegetables using modified QuEChERS combined with ultrahigh performance liquid chromatography-tandem mass spectrometry. (1st January 2019) - Dong, Hao; Xiao, Kaijun; Xian, Yanping; Wu, Yuluan; Zhu, Liang
Highlights: UPLC-MS/MS method was first developed for ClO4 −, BrO3 − analysis in fruit, vegetable. Modified QuEChERS was applied for effective purification before detection. No matrix-matched calibration is needed to compensate for matrix effects. Method has sufficient selectivity, sensitivity, accuracy to screen for 2 targets. ClO4 − was detected in several vegetables (concentrations: 21 μg/kg–162 μg/kg). Abstract: Perchlorate (ClO4 − ) and bromate (BrO3 − ) are mainly determined by ion chromatography methods. The present work aims to develop a modified QuEChERS combined with ultrahigh performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for simultaneous analysis of ClO4 − and BrO3 − in fruits and vegetables including cherry tomato, strawberry, tomato, potato, lettuce and pakchoi. Two target inorganic anions were separated on a Diamonsil C18(2) column by gradient elution, scanned in ESI negative mode and detected under multiple reactions monitoring (MRM). Limit of detection (LOD) and method limit of quantification (MLOQ), matrix effect, accuracy and precision of the developed method were investigated. Results were linear in their concentration ranges, with coefficients of determination ( r 2 ) bigger than 0.999. LODs for ClO4 − and BrO3 − were 0.1 μg/L and 0.5 μg/L, respectively. The validated method provided sufficient selectivity, sensitivity and accuracy to screen for ClO4 − and BrO3 − with ignorable matrix effects. Recoveries for different kinds of negative samples at 3 spiked levels were between 82.0% and 99.5%. Both intraday-precision and interday-precision were satisfactory, showing RSDr values in the range of 2.1–7.1% and RSDR values in the range of 7.2–10.8%. The proposed method was successfully applied to determine target inorganic anions in several fruits and vegetables. Perchlorate was detected in 12 vegetable samples with the concentrations ranged from 21 μg/kg to 162 μg/kg. Results indicated that there was wide ClO4 − contamination in vegetables, confirming its urgency for monitoring harmful inorganic anions in our daily consumed vegetables.